Nuclear delivery of NFκB-assisted DNA/polymer complexes: plasmid DNA quantitation by confocal laser scanning microscopy and evidence of nuclear polyplexes by FRET imaging - Breuzard, Gilles (Oxford University Press, 2008)
Quantification of a plasmid DNA (pDNA) and investigation of its polymer-associated state in the nucleus are crucial to evaluate the effectiveness of a gene-delivery system. This study was conducted with p3NF-luc-3NF, a pDNA-bearing optimized κB motif to favour NFκB-driven nuclear import. Here, a quantification of pDNA copies in the nucleus was performed by real-time confocal laser scanning microscopy in HeLa and C2C12 cells transfected with linear polyethylenimine or histidylated polylysine. Förster Resonance Energy Transfer (FRET) from the fluorescein-p3NF-luc-3NF donor to the co-localized rhodamine-polymer acceptor was carried out to investigate whether the pDNA was still condensed with the polymer in the nucleus. Upon 5 h of transfection, the nuclear amount of p3NF-luc3NF was ∼1500 copies in both cell lines whereas that of pTAL-luc, a 3NF-free counterpart pDNA, was less than 250. This quantity of p3NF-luc-3NF dropped dramatically to that of pTAL-luc in the presence of the BAY 11-7085, an inhibitor of NFκB activation. These data strongly support a nuclear import of p3NF-luc3NF mediated by NFκB. Moreover, FRET experiments clearly revealed that most of nuclear pDNA were still condensed with the polymer raising the question of their passage through the nuclear pore complex and their impact on the gene-expression efficiency.